Linum grandiflorum haplotype 1 assembly and gene annotation - Fracassetti, Marco; Zervakis, Panagiotis; Postel, Zoe; Losvik, Aleksandra; Soler, Lucile; Proux‐Wéra, Estelle; Bunikis, Ignas; Churcher, Allison; Slotte, Tanja (Stockholm University, 2026)
This dataset contains the fasta file (Lgrand_hap1_v1.fasta.gz) and the gene annotation (Lgrand_hap1_v1_genes.gff.gz) of Linum grandiflorum haplotype 1 assembly.

The annotated assembly has been deposited in the European Nucleotide Archive, ENA (Project PRJEB87190) but it is missing the assembly accession (GCA_123456). Only the EMBL file is present.

The genome assembly is based on PacBio HiFi and Hi-C data using Hifiasm (https://github.com/chhylp123/hifiasm).

The gene annotation has been done with MAKER (https://www.yandell-lab.org/software/maker.html) and manually curated by NBIS.

This dataset is associated with this article: Zervakis, P. I., Postel, Z., Losvik, A., Fracassetti, M., Solér, L., Proux‐Wéra, E., ... & Slotte, T. (2025). Genomic studies in Linum shed light on the evolution of the distyly supergene and the molecular basis of convergent floral evolution. New Phytologist, 247(6), 2964-2981.
Keywords: Evolutionary ecology; Medical and Health Sciences; Medicin och hälsovetenskap; Ecology; Ekologi